Human and Technology in the 21st Century - Ibanga, Isaac John (The Indonesian Institute of Science and Technology Research, 2024)
The 21st century witnesses an unprecedented surge in technological breakthroughs, profoundly reshaping human engagement with the world. Technology, from smartphones to artificial intelligence, permeates daily life, altering interactions and perceptions. This paper examines the multifaceted relationship between humanity and technology, exploring its implications, opportunities, and challenges. Technology enhances efficiency, communication, and access to information, catalyzing productivity and global connectivity. Key technological trends, including AI, IoT, blockchain, and renewable energy, reshape industries and societal dynamics. While technology offers benefits, it also poses challenges such as job displacement, privacy breaches, and health issues. To navigate the future, a balanced approach is essential, with initiatives promoting digital literacy and equitable access. Government regulations must safeguard privacy rights and foster ethical technology development. By embracing a human-centered approach, we can harness technology's promise while mitigating risks, steering toward an inclusive, equitable, and sustainable future.